HOW DIGITAL SKILLS AND TECHNOLOGY ADAPTATION SHAPE FEMALE GRADUATES' CAREER READINESS IN INDUSTRY 4.0? - Nadia Akhasha; Ahmad Shalahuddin; Arman Jaya; Nurul Komari; Mazayatul Mufrihah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study examines the effects of digital skills, technology adaptation, and ICT anxiety on the digital career readiness of female fresh graduates in Indonesia, with problem-solving skills as a mediating variable. Using a quantitative cross-sectional survey, data were collected from 205 respondents through an online questionnaire and analyzed with PLS-SEM using SmartPLS 4. The findings show that digital skills and technology adaptation positively and significantly influence problem-solving skills, while ICT anxiety has a significant negative effect. Problem-solving skills significantly enhance digital communication, collaboration, creativity, and production. Digital skills and technology adaptation also directly improve digital collaboration and creative output, whereas ICT anxiety has no significant direct effect on these outcomes. Mediation analysis indicates that problem-solving skills partially mediate the effects of digital skills and technology adaptation on digital performance, but not ICT anxiety. Overall, the results emphasize the importance of strengthening digital competencies, adaptive technology use, and problem-solving skills to enhance female graduates’ career readiness in the Industry 4.0 labor market.